Challenges in ABO-incompatible Renal Transplantation: A Case Report of Acute Antibody-mediated Rejection with Late Graft Thrombosis - Abhishek Pratap Singh; Pankaj Beniwal; Vinay Malhotra (Indian Journal of Transplantation)
Late graft thrombosis is an infrequent yet severe complication post renal transplantation, profoundly affecting graft survival and patient prognosis. We report a case of a 29-year-old male with end-stage renal disease due to IgA nephropathy who underwent ABO-incompatible renal transplantation. Despite effective desensitization, the patient experienced late graft thrombosis 3 months posttransplant, resulting in irreversible graft failure and necessitating hemodialysis initiation. This case underscores the complexities of late graft thrombosis and emphasizes the significance of timely identification and intervention for optimizing transplant outcomes.